PERCEIVED ORGANIZATIONAL SUPPORT AND HAPPINESS AT WORK: THE ROLE OF PSYCHOLOGICAL CAPITAL - ÖZDEMİR, Burak (Yonetim ve Ekonomi Arastirmalari Dergisi - Journal of Management and Economics Research, 2022)
Building on the tenets of social exchange theory and conservation of resources theory this study investigates the mediating role of psychological capital between organizational support and happiness at work. Data were collected from 207 white-collar workers of multiple organizations in Turkey. The findings indicate that perceived organizational support has moderate effect on happiness at work (work engagement, job satisfaction, affective commitment). Further, psychological capital mediates the relationship between perceived organizational supoort and work engagement. As a result, this study revealed that employees who perceive high levels of organizational support are more likely to generate positive psychological resources, which should lead to better work engagement. The findings of this study extend the social exchange theory and conservations of resource theory.
Keywords: 8. Economic growth